2015
DOI: 10.1007/s12061-015-9156-0
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Human Impact on Net Primary Productivity Using MODIS Data for Better Policy Making

Abstract: Tropical forests support core biological, hydrological and socioeconomic functions essential to life on earth. An assessment based on the Human Appropriation of Net Primary Production (HANPP) could help reduce exploitation of these forests, increasing their adaptive capacity and lessening their vulnerability to losses of Net Primary Productivity (NPP). Here we apply HANPP to the study area, based on Land Use Impact variability between the forest and contiguous roads and plantations by application of Geographic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 64 publications
(95 reference statements)
0
3
1
Order By: Relevance
“…The NPP model, which incorporated fAPAR, APAR, PAR and NDVI from satellite data, produced favourable outcomes for the NPP. In this study, the NPP evaluated for the plantation is 650 gCm -2 month -1 , higher than recorded by Razali et al (2015) in the tropical forest in Pasoh Forest Reserve in West Malaysia of 202.2 to 213.5 gCm -2 month -1 . The present model that utilizes NDVI data derived from WorldView-2 will be particularly valuable if applied to temporal NDVI data to assess the monthly NDVI for the study area.…”
Section: Npp Distributioncontrasting
confidence: 62%
“…The NPP model, which incorporated fAPAR, APAR, PAR and NDVI from satellite data, produced favourable outcomes for the NPP. In this study, the NPP evaluated for the plantation is 650 gCm -2 month -1 , higher than recorded by Razali et al (2015) in the tropical forest in Pasoh Forest Reserve in West Malaysia of 202.2 to 213.5 gCm -2 month -1 . The present model that utilizes NDVI data derived from WorldView-2 will be particularly valuable if applied to temporal NDVI data to assess the monthly NDVI for the study area.…”
Section: Npp Distributioncontrasting
confidence: 62%
“…There are several methods to quantitatively calculate the impact of human activities on NPP. Different land cover types (Saikku et al, 2015) or the human activity index can be used to calculate the sum of land use changes to obtain the anthropogenic effects on the NPP (Razali et al, 2015). The dynamic vegetation model has been used to evaluate the influence of human activities on the parameters of vegetation growth, which could then be used to quantify the effects (Ren et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The terrestrial NPP is directly relevant to humankind since it not only satisfies our needs for shelter, food and fuel, but also provides the energy to sustain the lives of other organisms that we depend on and controls the functioning of many ecosystem services (Field 2001, Daily 2013). Many studies have shown strong positive correlations between human population density and NPP (Chown et al 2003, Luck 2007, Razali et al 2016, Zhou et al 2021. In addition, globally, humans tend to settle in areas of medium to high NPP (Milesi et al 2005).…”
Section: Introductionmentioning
confidence: 99%